Software Innovations in Ultra-Wideband Technology: From Algorithms to Applications - Amit Sant, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transformative impact of Ultra-Wideband (UWB) technology in modern positioning and communication systems, with a particular focus on software innovations and implementations. The comprehensive article covers the evolution of UWB technology from its fundamental principles through advanced applications in both consumer and industrial sectors. The article explores sophisticated software architectures and algorithms that enable precise positioning and tracking capabilities, including statistical ranging methods and signal processing frameworks. It explores the development frameworks and integration protocols that have significantly improved system reliability and performance. The discussion encompasses both consumer applications, such as location-based gaming and augmented reality experiences, and industrial solutions, including smart home integration and digital key systems. The article addresses critical technical challenges in cross-platform compatibility, power consumption optimization, and environmental adaptation, providing detailed insights into implemented solutions. Furthermore, it examines future directions in UWB technology, particularly focusing on its integration with artificial intelligence and machine learning, while highlighting emerging applications in healthcare, robotics, and industrial IoT sectors.
Keywords: Ultra-Wideband Technology; Indoor Positioning Systems; Software Architecture; Real-time Tracking; Signal Processing